Escherichia coli as uropathogen: antibiotic susceptibility profiling - Jha, Anuja; Agrawal, Manju; Neral, Arvind; Hishikar, Rajesh; Maheshwari, Basant (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Empirically chosen antibiotics based on the local resistance pattern of uropathogens remain the principle treatment of urinary tract infections (UTI). Methods: Antibiogram of most frequent uropathogen was determined. Based on the antibiogram result, authors compared effectiveness of drugs recommended for UTI by National centre for disease control (NCDC), India, and assessed age and gender based variability in the effectiveness of these drugs. Results: 1278 urine samples were accounted, of which 405 samples showed significant growth. E. coli was the most common uropathogen (n=146, 36%) followed by enterococcus species (31%) and Klebsiella pneumoniae (10%). Using McNemar’s test authors found that nitrofurantoin (90% sensitivity) was statistically the most effective drug among drugs recommended by NCDC for uncomplicated cystitis. Furthermore, authors used Fisher’s exact test on adults and paediatrics and found that significant difference in effectiveness was observed for nitrofurantoin (p-value <0.001) and cotrimoxazole (p-value 0.034). Using logistic regression, authors found that with age, effectiveness of ciprofloxacin and cotrimoxazole deteriorate significantly (p-value 0.021 and 0.002 respectively). Additionally, authors observed that cotrimoxazole has significantly better efficacy in males compared to females (p-value 0.022). Conclusions: In accordance with present study, nitrofurantoin can be used as first line treatment for uncomplicated cystitis. Age and gender should be considered while prescribing empirical treatment for UTI. Periodic surveillance should be carried out to identify the on-going pattern of antibiogram to update the guideline for empirical therapy.